Effects of prolonged strenuous exercise (marathon running) on biochemical and haematological markers used in the investigation of patients in the emergency department. Issue 3 (21st May 2004) - Smith, J E; Garbutt, G; Lopes, P; Pedoe, D Tunstall
Abstract : Objectives: To investigate the effects of strenuous exercise on commonly used biochemical and haematological variables in subjects running the 2002 London marathon. Methods: 34 healthy volunteers (7 female, 27 male) were recruited for the study. Blood was taken before the start (at registration) and immediately after completion of the marathon. Samples were analysed for urea and electrolytes, liver function tests, creatine kinase (CK), CK-MB isoenzyme, myoglobin, troponin I, full blood count, a clotting screen, and D-dimers. The results before and after exercise were compared. Pearson's correlation coefficients were calculated for all variables. Results: Significant increases were found in CK, CK-MB, aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and myoglobin following the marathon. However, there was no significant change in the level of troponin I. There was also evidence of activation of the coagulation and fibrinolytic cascades following the marathon, with a reduction in activated partial thromboplastin time, a reduction in fibrinogen, and an increase in D-dimers. Conclusions: The results confirm previous individual studies on marathon running and the biochemical and haematological tests routinely carried out in hospital. These are affected by prolonged exercise, and "abnormal" results in these tests may be normal after prolonged exercise and therefore not diagnostic of a disease process. The results of investigations in patients who have been exercising should be interpreted with caution.